Dream theory from the perspective of Islam - Minoo, Asadzandi (International Journal of Psychotherapy Practice and Research, 2018)
Background and Objective: Sleep as a sign of the God wisdom and power, is the agent of stability and tranquility. Sleep has a spiritual dimension. Sincere dreams are the continuation of prophecy and guidance of the God. This study aimed to explain the dream theory from the perspective of Islam. Materials and Methods: This evolutionary study has focused on these questions: “what is the process of dreaming in Islam? Can people control their dreams”? Islamic evidences were taken from the verses and narrations related to the words “soul, sleep, dream and death”, using al-Mu’ayyim, authentic Shi’a commentary books, Bihar al-Anwar, Kofi principles, the Book of Resurrection and life after death. The religious and scientific evidences were analyzed based on the Walker and Event content analysis method. Dream theory was extracted from religious evidence. Results: Based on "revelation epistemology" during sleep, the ‘template of a higher universe’ travels to the unseen world and divine guidance can be provided. People with spiritual health) (owners of the Sound heart) can control the type of their dream, and solve problems by the guidance of God. In the perspective of Islam, there are three types of dreams: sometimes is divine guidance and glory from God, sometimes is sorrow from the devil, and sometimes are conflicts of daily living or past events. Conclusion: Regarding the spiritual aspect of sleep and its deep impact on physical and mental health, it is essential for medical staff to become familiar with dream theory from the perspective of Islam. They should explain to patients and family members the importance and impact of sleep on the acceleration of tissue repair and the treatment of anxiety and depression. To those who are willing to enjoy the divine guidance through the dream, they can teach the Islamic method of dream control.
Keywords: Islam; sleep; dream; soul; unseen word